Un satélite y la solución al problema de las telecomunicaciones en Colombia :| Åpodrá ser posible algún día? (2017)
Technological development has changed human interaction, which has converted many relationships that were of personal interaction, in virtual relationships. This is why it is understood that telecommunications are key to the development of countries today and it is also currently recognized that access to them is a human right. Within the diversity of the means for telecommunications, satellites prove to be an optimal alternative to obtain access in the countries with complicated geographic environments like the Colombian one. Colombia, having no satellite in orbit has serious difficulties in guaranteeing a plurality of rights associated with telecommunications. Given the above, the following research question will be presented in this text: What legal and economic implications are derived from the absence of a Colombian satellite, and how does it affect the economic and social development of the country? The answer is that, due to the fact that telecommunications are key to the development of the countries, Colombia would obtain enormous benefits from the placement of a satellite that could cover all areas of the national territory.